ANALISIS TEKNOLOGI HIBRID DI SCIENCE TECHNO PARK PROVINSI SUMATERA SELATAN - Bizzy, Irwin; Syamsul, Syamsul; Cornely, Epina; Kurniawan, Bayu; Apriyan, Dian (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2020)
The hybrid technology here is a combination of technology derived from solar energy and biogas from cow dung. Each cow shed has a roof that can be installed with solar cells to generate electricity, and cow dung can be used as a source of biogas energy, which can also be converted into electrical energy. This hybrid technology is one of the new renewable energy potentials in an environmentally friendly future.